Mine, Ours or Yours? Unintended Framing Effects in Dictator Games - Andreas Bergh; Philipp Christoph Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper reports results from a classroom dictator game comparing the effects of three different sets of standard instructions. The results show that seemingly small differences in instructions induce fundamentally different perceptions regarding entitlement. Behavior is affected accordingly, i.e. instructions inducing subjects to perceive the task as distributive rather than a task of generosity lead to higher allocations to receivers (average 52% vs. 35%). A theoretical explanation integrating monetary as well as social incentives and emphasizing potential effects of uncertainty about the latter is discussed (cf. Bergh and Wichardt, 2018).
Keywords: C70; C91; D63; 330; dictator games; framing effects; property rights; social preferences